INVESTIGATION OF CEMENT CONCRETE CONGLOMERATE SOLIDIFICATION PROCESS BY IMPEDANCE SPECTROSCOPY METHOD - S. N. Bandarenka; P. V. Chulkin; G. A. Ragoisha; A. O. Kolikov; A. S. Bandarenka (Наука и техника)
One of the most prospective directions in preservation  and increase of service live of  road pavements is a construction of  automobile roads with cement concrete surface. Modern tendencies for provision of road construction quality presuppose a necessity to control processes of solidification and subsequent destruction of the material while forming and using cement concrete conglomerate being considered as a basic element of the road surface.  Multiyear practical experience of  automobile road operation using cement concrete pavements reveals an importance for monitoring  such processes as formation and destruction of cement concrete materials. An impedance spectroscopy method has been tried out and proposed as a tool for solution of the given problem.Experimental samples of cement concrete have been prepared for execution of tests, graded silica sand and granite chippings with particle size from 0.63 to 2.5 mm have been used as a fine aggregate in the samples. Dependencies of resistance (impedance) on AC-current frequency  have been studied for samples of various nature and granulometric composition. The Gamry  G300 potentiostat has been used for measurement of complex impedance value. A spectrum analysis and calculation of equivalent circuit parameters calculation have been carried out while using EIS Spectrum Analyzer program.Comparison of impedance spectra for the prepared cement concrete samples have made it possible to reveal tendencies in changing spectrum parameters during solidification and subsequent contact with moisture in respect of every type of the sample. An equivalent electrical circuit has been developed that  characterizes physical and chemical processes which are accompanied by charge transfer in cement concrete conglomerate. The paper demonstrates a possibility to use an impedance spectroscopy for solution of a number of actual problems in the field of cement concrete technology problems. Particularly, the problems are connected with usage of technogenic wastes (e.g. granite chippings as a fine aggregate) and optimization of mineral and granulometric mix composition for road pavement. Development of an approach for investigation of properties on cement concrete materials on the basis of an impedance spectrum analysis will permit  quantitatively to characterize processes which are occurring in them including such processes as concrete solidification and corrosion.